Modeling and Control of an 8-Legged Stewart Platform Using Null-Space Control for Precise Motion Under Actuator Constraints - Siradjuddin, Indrazno; Fitria, Ida Lailatul; Al Azhar, Gillang; Riskitasari, Septyana; Ronilaya, Ferdian; Wicaksono, Rendi Pambudi (Journal of Robotics and Control (JRC), 2025)
This paper investigates the modeling, control, and redundancy resolution of an 8-legged Stewart platform, emphasizing the use of null-space control to achieve precise trajectory tracking while adhering to actuator constraints. The proposed control framework combines a Proportional-Integral-Derivative (PID) controller with null-space projection to exploit the platform’s inherent redundancy for secondary objectives, such as singularity avoidance, energy optimization, and enhanced fault tolerance. A clamping strategy ensures that actuator lengths remain within operational limits, thereby preventing mechanical failures. Simulation results demonstrate significant error reduction in both position and orientation, even under strict actuator constraints. Specifically, the system achieved exponential convergence to the desired pose within 3 s, with a maximum position error of less than 1 × 10−3 m and orientation error below 5 × 10−4 rad. Actuator efficiency was also enhanced, as the algorithm dynamically redistributed efforts among actuators to avoid overloading any single leg. While energy consumption was not explicitly optimized in this study, the framework provides a foundation for future work in minimizing energy usage through advanced secondary objectives. Stability is analyzed rigorously using Lyapunov’s direct method. Compared to traditional six-legged platforms, the 8- legged design offers superior flexibility and adaptability, making it particularly suitable for applications in flight simulators, robotic surgery, and industrial automation where precision and reliability are critical. However, the proposed approach has certain limitations. For instance, the current implementation assumes ideal actuator dynamics and does not account for uncertainties such as friction, backlash, or external disturbances. Additionally, the clamping strategy may introduce computational overhead, potentially impacting real-time performance in highly dynamic scenarios. Future research could address these limitations by incorporating adaptive or robust control techniques and optimizing computational efficiency. This work advances the design and control of redundant parallel manipulators, offering practical insights into dealing with physical limitations and providing a foundation for future innovations in high-performance motion control systems.